Identifikasi Upaya Terapeutik Pengentasan Kecemasan Berdasarkan Pemikiran Al-Ghazali - Nurlaila Qadriah Yunan; Muslihati Muslihati; M. Ramli (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: On this era, people often feel over anxiety in face their life. In this case be defiance for counselor to effort the preventive prevention and raise the anxiety abundant. The purpose of this research is to get data of texts which are related to the anxiety healing target based on Al-Ghazali thingking text. This research uses qualitative approach with analysis content primer data in this research is Al-Ghazali thingking text through his huge works and secunder data was got from an informant which is in this case he is a ustadz (expert spiritual) who has learned about Al-Ghazali thingking text. the result of this research found some descriptive-interpretive explanation about meaning of anxiety, cause of anxiety, characteristic of anxiety and determined by some interventions as the effort of anxiety healing such as: (1) thinking theraphy and (2) good behavior (amal shalih) theraphy. Abstrak: Pada era yang begitu cepat ini manusia semakin sering mengalami kecemasan yang berlebihan dalam menghadapi kehidupannya. Hal ini menjadi tantangan bagi konselor dalam upaya pencegahan serta pengentasan kecemasan berlebihan tersebut. Tujuan penelitian ini adalah memperoleh sejumlah data teks yang berkenaan dengan sasaran pengentasan kecemasan berdasarkan teks pemikiran Al-Ghazali. Penelitian ini menggunakan pendekatan kualitatif, dengan metode content analysis. Data primer dalam penelitian ini adalah teks pemikiran Al-Ghazali melalui karya-karya besarnya, dan data sekunder diperoleh dari informan yaitu ustadz yang mendalami teks pemikiran Al-Ghazali. Hasil penelitian ini ditemukan sejumlah keterangan deskriptif-interpretif tentang hakikat kecemasan, penyebab kecemasan, ciri-ciri kecemasan, dan intervensi sebagai upaya pengentasan kecemasan, yaitu melalui (1) terapi berpikir dan (2) terapi amal shalih.